2023
DOI: 10.18632/aging.204738
|View full text |Cite
|
Sign up to set email alerts
|

Plasma exosome proteomics reveals the pathogenesis mechanism of post-stroke cognitive impairment

Abstract: Exploration and utilization of exosome biomarkers and their related functions provide the possibility for the diagnosis and treatment of post-stroke cognitive impairment (PSCI). To identify the new diagnostic and prognostic biomarkers of plasma exosome were uzed label-free quantitative proteomics and biological information analysis in PSCI patients. Behavioral assessments were performed, including the Mini-Mental Status Examination (MMSE), the Montreal Cognitive Assessment (MoCA), the Barthel index, the Morse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…YWHAZ, part of the 14–3–3 protein family, affects cellular proliferation, migration, and differentiation by interacting with phosphoserine- and serine-containing proteins . Clinically, elevated levels of YWHAZ poststroke have been associated with cognitive impairment, while experimental models demonstrate that reduced YWHAZ expression leads to neurodevelopmental and cognitive deficits . Our study establishes the significance of five proteins in ischemic stroke, highlighting their potential as biomarkers and therapeutic targets.…”
Section: Discussionsupporting
confidence: 54%
“…YWHAZ, part of the 14–3–3 protein family, affects cellular proliferation, migration, and differentiation by interacting with phosphoserine- and serine-containing proteins . Clinically, elevated levels of YWHAZ poststroke have been associated with cognitive impairment, while experimental models demonstrate that reduced YWHAZ expression leads to neurodevelopmental and cognitive deficits . Our study establishes the significance of five proteins in ischemic stroke, highlighting their potential as biomarkers and therapeutic targets.…”
Section: Discussionsupporting
confidence: 54%
“…According to Qi et al (2023) , 31 proteins that were up-regulated in PSCI patients compared to controls may be connected to platelet aggregation and coagulation, whereas 128 proteins that were down-regulated may be connected to pathways such complement activation, fibrin clotting, and cell adhesion protein binding. However, a quantitative proteomics study of plasma in patients with lacunar infarction identified 112 proteins associated with cognitive decline ( Datta et al, 2022 ), most of which were not associated with inflammation, complement activation, coagulation, fibrinolysis, or endothelium.…”
Section: Resultsmentioning
confidence: 99%
“…YWHAZ, part of the 14-3-3 protein family, affects cellular proliferation, migration, and differentiation by interacting with phosphoserine-and serine-containing proteins (Aghazadeh & Papadopoulos, 2016). Clinically, elevated levels of YWHAZ post-stroke have been associated with cognitive impairment (Qi et al, 2023), while experimental models demonstrate that reduced YWHAZ expression leads to neurodevelopmental and cognitive deficits (Wan et al, 2023). Our study establishes the significance of five proteins in in ischemic stroke, highlighting their potential as biomarkers and therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%